Eliciting and Understanding Primary Care and Specialist Mental Models of Cirrhosis Care: A Cognitive Task Analysis Study - Tanya Barber; Lynn Toon; Puneeta Tandon; Lee A. Green (Canadian Journal of Gastroenterology and Hepatology)
Background. Gaps in coordination and transitions of care for liver cirrhosis contribute to high rates of hospital readmissions and inadequate quality of care. Understanding the differences in the mental models held by specialty and primary care physicians may help to identify the root causes of problems in the coordination of cirrhosis care. Aim. To compare and identify differences in the mental models of cirrhosis care held by primary and specialty care physicians and nurse practitioners that may be addressed to improve coordination and transitions. Methods. Cross-sectional formal elicitation of mental models using Cognitive Task Analysis. Purposive and chain-referral sampling to select family physicians (n = 8), specialists (n = 9), and cirrhosis-dedicated nurse practitioners (n = 2) across Alberta. Results. Family physicians do not maintain rich mental models of cirrhosis care. They see cirrhosis patients relatively infrequently, rebuilding their mental models when required (knowledge on demand). They have reactive and patient-need-focused, rather than proactive and system-of-care, mental models. Specialists’ mental models are rich but vary widely between patient-centered and task-centered and in the degree to which they incorporate responsibility for addressing system gaps. Nurse practitioners hold patient-centered mental models like specialists but take responsibility for addressing gaps in the system. Conclusions. Improving the coordination of cirrhosis care will require infrastructure to design care pathways and work processes that will support family physicians’ knowledge-on-demand needs, facilitate primary care-specialist relationships, and deliberately work toward building a shared mental model of responsibilities for addressing medical care and social determinants of health.